A near-infrared carbon dioxide sensor system using a compact folded optical structure for deep-sea natural gas hydrate exploration. Issue 39 (2nd October 2018) - Liu, Zhiwei; Zheng, Chuantao; Chen, Chen; Xie, Hongtao; Ren, Qiang; Ye, Weilin; Wang, Yiding; Tittel, Frank K.
Abstract : A near-infrared carbon dioxide sensor system using a compact folded optical structure for deep-sea natural gas hydrate exploration. Abstract : The detection of dissolved gas ( e.g. carbon dioxide (CO2 ) and methane (CH4 )) in seawater is important for deep-sea natural gas hydrate exploration, which requires that the sensor especially the optical structure should be of compact size and capable of operation in a deep-sea environment. A compact optical structure with a simple beam alignment and tracing method was proposed for tunable laser absorption spectroscopy (TLAS) based gas measurements, in order to minimize the sensor size and ease the beam alignment/tracing procedure for deep-sea operation. A near-infrared CO2 sensor system was developed based on the compact optical structure. A distributed feedback (DFB) laser centered at 6361.3 cm −1 and a multi-pass gas cell (MPGC) with an effective optical path length of 29.8 m were employed. The sensor system was integrated as standalone equipment by customizing an aluminum baseplate for a stable field operation. A series of experiments were carried out to assess the performance of the sensor system. A limit of detection (LoD) of ∼7.1 parts-per-million in volume (ppmv) at a 0.4 s averaging time was obtained, and the LoD was reduced to ∼277 parts-per-billion in volume (ppbv) at an optimum averaging time of 153.6 s. Considering the gas mixing time, the rise and fall times were measured to be ∼290 s and ∼200 s, respectively. The proposed compact sensor structure provides the basis for the further development of a sensor system for dissolved CO2 detection with a LoD of ppbv via the use of a mid-infrared tunable laser.